Evaluation and implementation of highly challenging balance training in clinical practice for people with Parkinson's disease: protocol for the HiBalance effectiveness-implementation trial. Issue 1 (December 2017) - Leavy, Breiffni; Kwak, Lydia; Hagströmer, Maria; Franzén, Erika
Abstract Background If people with progressive neurological diseases are to avail of evidence-based rehabilitation, programs found effective in randomized controlled trials (RCT's) must firstly be adapted and tested in clinical effectiveness studies as a means of strengthening their evidence base. This paper describes the protocol for an effectiveness-implementation trial that will assess the clinical effectiveness of a highly challenging balance training program (the HiBalance program) for people with mild-moderate Parkinson's disease (PD) while simultaneously collecting data concerning the way in which the program is implemented. The HiBalance program is systemically designed to target balance impairments in PD and has been shown effective at improving balance control and gait in a previous RCT. Study aims are to i) determine the effectiveness of the adapted HiBalance program on performance and self-rated outcomes such as balance control, gait and physical activity level ii) conduct a process evaluation of program implementation at the various clinics iii) determine barriers and facilitators to program implementation in these settings. Methods This effectiveness-implementation type 1 hybrid study will use a non-randomized controlled design with consecutive inclusion of people with PD at multiple clinical sites. A mixed method approach will be used to collect clinical effectiveness data and process evaluation data which is both quantitative and qualitative in nature. The consolidated framework for implementation research (CFIR) will be used to guide the planning and collection of data concerning implementation barriers and facilitators. The HiBalance program will be provided by physical therapists as a part of standard rehabilitation care at the clinical sites, while the evaluation of the implementation process will be performed by the research group and funded by research grants. Discussion An effectiveness-implementation study design benefits patients by speeding up the process of translating findings from research settings to routine health care. Findings from this study will also be highly relevant for those working with neurological rehabilitation when faced with decisions concerning the translation of training programs from efficacy studies to everyday clinical practice. Trial registration ClinicalTrials.gov march 2016, NCT02727478 .